Installation Optimization on the Tilt and Azimuth Angles of the Solar Heating Collectors for High Altitude Towns in Western Sichuan. (2017) - Jin, Zhenghao; Xu, Kuo; Zhang, Yin; Xiao, Xuefei; Zhou, Jing; Long, Enshen
Abstract: The solar resource is abundant in the western Sichuan area of China, which is accompanied by the high altitude and cold climate. With the optimization purpose of the maximum solar energy collection over the year and in winter season, the optimum tilt and azimuth angles of the solar collection panels were analyzed in this paper, under the background of the six high altitude towns in this area. The installation angle of the solar heating collector had remarkable influence on the solar radiation collection, and the optimum tilt angles in winter season were 10°-20° larger than that over the year, while the optimum azimuth angles varied limitedly with the temporal and spatial variations. Results in this paper, on the one hand, had clarified the fitness of the recommending variation ranges in the solar collector installation angels which proposed in current standards, which recommended the azimuth angle should be ranged from -20° to +20° and the tilt angle should be within latitude±25°. On the other hand, the maximum decrement of the solar energy collection can amount to as high as 29.5% for the tilt angles and 6.5% for the azimuth angles, if choosing the installation angles arbitrarily within the recommending variation ranges. In addition, this paper had further proposed that, the key factor in affecting the variations of the optimum tilt and azimuth angles was the regional composite feature of the solar radiation, validating the importance of the regional optimization design in improving the solar energy collection locally.